Percutaneous radiofrequency ablation in osteoid osteoma: Tips and tricks in special scenarios. Issue 102 (May 2018) - Esteban Cuesta, Helena; Martel Villagran, José; Bueno Horcajadas, Angel; Kassarjian, Ara; Rodriguez Caravaca, Gil
Abstract: Objectives: To define specific characteristics of osteoid osteomas treated with radiofrequency ablation, that may benefit from special technical recommendations. Methods: Retrospective analysis of all radiofrequency ablations performed by our group from January 2001 to March 2015. A descriptive study was conducted. We compared our results with the available literature to determine the most frequent special scenarios. Results: 207 radiofrequency ablations were performed in 200 patients. We defined the following scenarios: osteoid osteomas located in the spine, close to neurovacular structures, osteoid osteomas in small bones (hands and feet), intra-articular, deeply located or superficial and lesions with extensive periosteal reaction. Conclusions: The scenarios defined required special considerations and technical variations. Implementing the different tips and tricks shown in the article, the most complex osteoid osteomas could be successfully ablated.